Revisiting the effective exchange rates of the euro - Martin Schmitz; Maarten De Clercq; Michael Fidora; Bernadette Lauro; Cristina Pinheiro (European Central Bank (ECB), 2012)
This paper describes in detail the methodology currently used by the European Central Bank (ECB) to determine the nominal and real effective exchange rate indices of the euro. Building on the work of Buldorini et al. (2002), it shows how the ECB's techniques for calculating effective exchange rates have been updated over time and explains the related theoretical foundations. In particular, the paper discusses the use and development of trade weights based on trade in manufactured goods (taking account of third market effects), the trading partners selected, and the choice of deflators for constructing the real effective exchange rate indices. In addition, it presents evidence on exchange rate and competitiveness developments for both the euro area as a whole and individual Member States. While the growing importance of China is reflected in the updated trade weights of euro effective exchange rates, it appears that the increasing integration of the euro area with other European economies accounts for the largest variation in trade weights. The US dollar, an anchor currency for a number of large emerging markets, continues to play an important role for the effective exchange rate of the euro and euro area competitiveness. Overall, euro area competitiveness has improved slightly since the introduction of the single currency, despite significant heterogeneity within the euro area.
Keywords: C43; D12; E31; 330; competitiveness; EER; HCI; NEER; REER; trade weights